Differential Response of Central Blood Pressure to Isometric and Isotonic Exercises - Tanaka, Satoru (Nature Publishing Group, 2014)
Central blood pressure may be more closely associated with cardiovascular events than peripheral blood pressure. The aim of the present study was to investigate central blood pressure responses to exercise. Apparently healthy 18 subjects were enrolled in the study (38 ± 6 years) and changes in central and brachial blood pressure were recorded in response to ergometer and hand-grip exercises. Central blood pressure was estimated using an automated device (Omron HEM-9000AI). Systolic brachial blood pressure was increased after both ergometer (from 119 ± 10 to 172 ± 16 mmHg; P < 0.001) and hand-grip (from 118 ± 8 to 122 ± 9 mmHg; P = 0.001) exercises, but central systolic blood pressure was increased only after hand-grip exercise (from 117 ± 11 to 121 ± 12 mmHg; P = 0.002). The radial augmentation index was increased after hand-grip exercise, whereas ergometer exercise reduced this index. Heart rate was increased only after ergometer exercise. Thus, isometric, but not isotonic, exercise may increase central blood pressure in overall healthy subjects. The response of central blood pressure, which is a better index of cardiac load than peripheral blood pressure, to hand-grip exercise may be useful in evaluating cardiovascular risk.